ROLE OF JALOUKAVACHARAN IN THROMBOSED HEMORRHOIDS- A CASE STUDY - Sarika, Singh; Kedar Nita, M; Raut Subhash, Y; Lakhapati Aru, M (International Journal of Ayurveda and Pharma Research, 2015)
Todays fast and developing age blessed us with many improved life aids. But along with this todays lifestyle given us many ailments. Hemorrhoids are one of them which affect all economical groups of population. Hemorrhoids are dilatation of rectal veins. Thrombosed Hemorrhoid is a very painful and extremely uncomfortable condition. This condition worsen when strangulation develops that cutoffs blood supply. Typically a clot of blood making it very painful. According to Ayurveda Arsha (hemorrhoids) is defined as Maanski (External hemorrhoids) that obstructs anal opening causing severe pain during defecation like an enemy. Aacharya Sushruta mentioned Jaloukavacharan as treatment of choice in this painful condition. In the presented case we applied Jalouka on thrombosed hemorrhoids. This application provides local analgesic, thrombolytic and anti-inflammatory action along with significant symptomatic improvement to the patient.